2016
DOI: 10.1111/ped.13185
|View full text |Cite
|
Sign up to set email alerts
|

Fecal retention in childhood: Evaluation on ultrasonography

Abstract: Ultrasound rectal diameter measurement can be used to detect fecal retention in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 14 publications
2
15
1
1
Order By: Relevance
“…Singh et al found that rectal crescent size in children with constipation was 3.4 versus 2.4 in healthy control subjects (21) . Contrary to studies conducted by Hatori et al (20) , Karaman et al (19) , and Doniger et al (16) , a systematic review of four studies by Berger et al found insufficient evidence regarding the clinical importance of the relationship between clinical symptoms of constipation and rectal diameter on transabdominal sonography (22) .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Singh et al found that rectal crescent size in children with constipation was 3.4 versus 2.4 in healthy control subjects (21) . Contrary to studies conducted by Hatori et al (20) , Karaman et al (19) , and Doniger et al (16) , a systematic review of four studies by Berger et al found insufficient evidence regarding the clinical importance of the relationship between clinical symptoms of constipation and rectal diameter on transabdominal sonography (22) .…”
Section: Discussionmentioning
confidence: 91%
“…In a study by Hatori et al, children with fecal retention had a rectal diameter larger than that of children without constipation. The cutoff value was 27 mm at the level of symphysis pubis with high sensitivity and specificity (95.5% and 94.1%, respectively) (20) . Singh et al found that rectal crescent size in children with constipation was 3.4 versus 2.4 in healthy control subjects (21) .…”
Section: Discussionmentioning
confidence: 98%
“…The pelvic US was used in similar studies to evaluate rectal diameter in children (9)(10)(11)13,14). Children with normal defecation patterns in the studies by Joensson at al.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies have reported cases for which a US technique was used to diagnose constipation for measuring the rectal diameter in children. US images show a fecal mass in the rectum as a crescent-shaped acoustic shadow (9)(10)(11)(12)(13)(14). Several authors have proposed the use of US as a firstline clinical imaging and initial diagnostic technique for colon (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Eine abdominelle Sonografie erfolgt zur Einschätzung von Schweregrad und Chronizität unter der Fragestellung: Kolondilatation, Rektumdilatation (transversaler Diameter >27 mm spricht für Stuhlretention, zudem guter Verlaufsparameter [5]), Restharn, Auffälligkeiten der Nieren und oder der ableitenden Harnwege.…”
Section: Sonografie Abdomenunclassified